2019
DOI: 10.1093/ajcn/nqz028
|View full text |Cite|
|
Sign up to set email alerts
|

Model of personalized postprandial glycemic response to food developed for an Israeli cohort predicts responses in Midwestern American individuals

Abstract: Background Controlled glycemic concentrations are associated with a lower risk of conditions such as cardiovascular disease and diabetes. Models commonly used to guide interventions to control the glycemic response to food have low efficacy, with recent clinical guidelines arguing for the use of personalized approaches. Objective We tested the efficacy of a predictive model of personalized postprandial glycemic response to fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 44 publications
4
51
0
Order By: Relevance
“…), personalized nutrition is a new therapeutic possibility for prevention and control of disease [230]. Recent studies of cohorts have revealed great differences in post-meal glucose levels between individuals eating the same mealtimes [229,231].…”
Section: Personalized Nutritionmentioning
confidence: 99%
“…), personalized nutrition is a new therapeutic possibility for prevention and control of disease [230]. Recent studies of cohorts have revealed great differences in post-meal glucose levels between individuals eating the same mealtimes [229,231].…”
Section: Personalized Nutritionmentioning
confidence: 99%
“…Complex algorithms based on clinical, phenotypic, and microbial data can now predict glycemic response in ways that outperform traditional dietary approaches that historically relied on information specific to the caloric and carbohydrate content of food. [20][21][22] The success of this work provides proof of principle in support of the future benefits of personalized nutrition. 23 Lastly, it should be clearly stated that we do not expect hydrogen sulfide to be the only story relevant to colon neoplasia formation.…”
Section: Gut Microbiome and Colon Cancermentioning
confidence: 75%
“…Precision nutrition approaches are being developed to personalize an individual's diet to minimize CGM measured glycemic responses to meals (Mendes-Soares et al, 2019;Zeevi et al, 2015). An implicit assumption that has not previously been investigated is that the ranking of an individual's meals by glycemic response is relatively independent of the CGM used to make the measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Postprandial glucose is believed to play an important role in health and disease (Blaak et al, 2012;Hall et al, 2018) and precision nutrition approaches are being developed to personalize an individual's diet to minimize postprandial glycemic responses measured using continuous glucose monitors (CGMs) (Mendes-Soares et al, 2019;Zeevi et al, 2015). However, it is unclear to what extent different CGMs provide discordant meal rankings in terms of glycemic response and therefore whether personalized diets might be CGM dependent.…”
Section: Introductionmentioning
confidence: 99%